Digital Technology as a Strategic Driver of Competitive Advantage Hospital: Evidence from the Mediating Role of Digital Infrastructure : Teknologi Digital sebagai Penggerak Strategis Keunggulan Kompetitif Rumah Sakit: Bukti dari Peran Mediasi Infrastruktur Digital - Dina Ediana; Felina C. Young; Hector Jhon T. Manaligod (OGZ Research & Publishing, 2026)
Abstract: Hospitals in Bukittinggi face challenges in increasing competition and patient expectations. This study shows that hospitals in Bukittinggi are facing challenges in increasing their competitiveness amid high competition and patient expectations, where the development of digital technology and digital infrastructure are key factors in increasing competitive advantage through service efficiency and innovation. Objective : This study analyzes the impact of digital technology, its use, and digital infrastructure on the competitive advantage of hospitals in Bukittinggi City, West Sumatra. Digital transformation in the healthcare sector is increasingly important in improving operational efficiency, service quality, and the speed of clinical processes. However, initial observations indicate that most hospitals in Bukittinggi still face various obstacles, such as inadequate technological infrastructure, low digital literacy among healthcare workers, unintegrated digital systems, and resistance to change. These conditions result in suboptimal service processes and hinder the achievement of hospital competitive advantage. Methodology : This study uses a quantitative approach with the Structural Equation Modeling (SEM-PLS) method to test the direct and indirect effects between variables. Research Results : The results of the hypothesis testing show that digital technology has a significant impact on digital infrastructure. Digital infrastructure has a significant impact on competitive advantage. Digital technology has an indirect effect on the competitive advantages of hospitals through the digital infrastructure path